الصحافة الالكترونية الدينية، دراسة وصفية نقدية - رقية, بوسنان (Sciences de l'Homme et de la Société, 2017)
هدفت الدراسة إلى تحليل مضمون الصحافة الدينية الالكترونية كشكل جديد من الصحافة الذي نشأ مع تطور شبكة الانترنت، وقد شمل التحليل الصحافة الدينية المتوفرة على الشبكة والمنتمينة لمتتلنا الندول الير،ينة، وشمنل التحلينل انينة أعداد، وأظهرت نتائج الدراسة أنه مقارنة ،الصحافة الير،ية واليلمينة فن ن الكن اليننددي للصننحافة ايسنن مية لا يكنناد يننذكر ، وأن ،يننتج رننارص الصننحافة الالكترونيننة الدينيننة توقننا تسننباص تتيلنن ،التم ويننل والاسننت مار ف ال ضننا ايلكتروني وتوقيا ،يتج النسخ الورقية. Abstract: The study aimed to analyse the content of the e-religious press as a new form of journalism, who grew up with the evolution of the Internet. The analysis has included the religious press available on the network and that belongs to the different Arab countries, as it also included 80 number and the study results showed that comparing to the Arab and scientific journalism, the numerical quantum of the Islamic press is negligible, and that some religious electronic media experiences have stopped for reasons of financing and investing in cyberspace and the arrest of some hard copies.